The ACCA accreditation in Poland – accounting educators’ perspective - Biernacki, Michał; Krasodomska, Joanna; Zarzycka, Ewelina (Akredytacja ACCA w Polsce – perspektywa edukatorów rachunkowości, 2019)
Organizations certifying accountants, such as the Association of Chartered Certified Accountants (ACCA), play an important role in strengthening their professional status. Being accredited by them has recently become the goal of many institutions which offer accounting programs. Our paper aims to investigate the impact of ACCA accreditation on the accounting education in Poland, as well as to identify the important aspects of the collaboration between ACCA and accounting educators. The findings are based on a survey conducted among 50 faculty members from seven Polish universities. According to the respondents the accreditation increases the prestige of the offered teaching programs and has an important impact on the organization of exams taken by the students participating in accredited courses. The ACCA engagement in collaboration with universities consists mostly in promotion of the accredited programs. Despite some limitation the study provides new insights into the problem of accounting education in the accreditation processes context
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 4, s. 1-9
Keywords: accounting education; accreditation; ACCA; akredytacja; nauka rachunkowości